Perceived organizational support, career satisfaction, and performance outcomes A study of hotel employees in Cameroon - Karatepe, Osman M. (Emerald Group Publishing Limited, 2012)
Purpose - The purpose of this study is to develop and test a research model that examines career satisfaction as a mediator of the effect of perceived organizational support on service recovery performance and job performance. Design/methodology/approach - Based on data obtained from frontline hotel employees with a time lag of one month and their immediate supervisors in Cameroon, the hypothesized relationships were tested using LISREL 8.30 through structural equation modeling. Findings - The results suggested that the fully mediated model had a better fit to the data when compared to the partially mediated model. As hypothesized, perceived organizational support influenced service recovery performance and job performance only via career satisfaction. Research limitations/implications - Investigating the study relationships over a longer period of time than was done in this study would be useful for making causal inferences conclusively. Replication studies with larger sample sizes in different hospitality and tourism settings in Cameroon and other countries in sub-Saharan Africa would be beneficial for broadening the database for further generalizations. Practical implications - Managers should make sure that they recognize employees' good work or efforts continuously. They should also ensure that employees participate in decisions that may affect the service delivery process It is also critical to have a pool of employees with work experience gained in foreign countries. Employees who worked in other hotels in foreign countries would acquire new skills and thus have higher career satisfaction in the current organization. Originality/value - This study contributes to the hospitality management and marketing literature by examining the mediating role of career satisfaction in the relationship between perceived organizational support and two organizationally valued performance outcomes, i.e. service recovery performance and job performance.
Keywords: Cameroon; Career satisfaction; Hotel employees; Perceived organizational support; Performance measurement (quality); Hospitality services; Hospitality management; Employees involvement